2003
DOI: 10.1128/aac.47.5.1589-1597.2003
|View full text |Cite
|
Sign up to set email alerts
|

Lysostaphin Cream Eradicates Staphylococcus aureus Nasal Colonization in a Cotton Rat Model

Abstract: The anterior nares are a primary ecologic niche for Staphylococcus aureus, and nasal colonization by this opportunistic pathogen increases the risk of development of S. aureus infection. Clearance of S. aureus nasal colonization greatly reduces this risk. Mupirocin ointment is the current standard of care for clearance of S. aureus nasal colonization, but resistance to this antibiotic is emerging. Lysostaphin is a glycylglycine endopeptidase which specifically cleaves the cross-linking pentaglycine bridges in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(122 citation statements)
references
References 52 publications
3
117
2
Order By: Relevance
“…Nasal colonization by S. aureus strains was determined using a cotton rat model as described previously (29). Comparison of strains was evaluated on the recovery of bacteria using Student's t test.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal colonization by S. aureus strains was determined using a cotton rat model as described previously (29). Comparison of strains was evaluated on the recovery of bacteria using Student's t test.…”
Section: Methodsmentioning
confidence: 99%
“…There is a significant link between S. aureus nasal colonization and development of S. aureus infections (29). The cotton rat (Sigmodon hispidus) has been used to study human respiratory pathogens, due to its susceptibility to human diseases and similarity in disease progression and its epithelial tissue, which is comparable to that of humans (29). Nasal colonization by ahpC and katA mutants and the wild type was tested as described previously (10).…”
Section: Vol 189 2007 Peroxide Stress Resistance Proteins Of S Aurmentioning
confidence: 99%
“…Beeswax was obtained from Shanghai Herb&Bee products Co., Ltd (Shanghai, China). Lysostaphin (139 U/mg) was produced by Shanghai High-Tech United Biological R&D Co., Ltd (Shanghai, China); 5 mg/g lysostaphin formulated in a petrolatum-based cream (LPC) was prepared by the method based on Kokai-Kun et al (2003).…”
Section: Methodsmentioning
confidence: 99%
“…However, Amidi et al (2010) reviewed that the short residence time of the current formulations in the nasal cavity due to mucociliary clearance posed a severe limitation for the drug delivery in the nasal cavity. Kokai-Kun et al (2003) and Walsh et al (2004) prepared a semi-solid cream and found that the cream greatly enhanced the efficacy of lysostaphin against S.aureus nasal colonization in cotton rats. Walsh et al (2004) also prepared a chitosan formulation and found that the formulation could significantly prolong the residence time of lysostaphin in the nose.…”
Section: Introductionmentioning
confidence: 99%
“…Lysostaphin has a maximum bactericidal concentration of 0.16-2.5µg/ml against MRSA [151]. Lysostaphin-based products have been developed for clinical trials in the USA by Biosynexus Inc. [152]. Clinical antibiotic-resistant S. aureus exhibited sensitivity to recombinant lysostaphin, highlighting the pre-clinical efficacy of the enzyme as an antibiotic [153].…”
Section: Enzymibioticsmentioning
confidence: 99%